A taxonomy of initiatives at work in the sharing economy. Issue 3 (August 2020) - Fernandes, Bruno; Chimenti, Paula; Nogueira, Roberto
Highlights: A taxonomy of initiatives at work in Sharing Economy is proposed with five categories. Commodity and unique-service intermediaries emerged as different categories. Blockchain has enabled the emergence of decentralized commodity intermediaries. Abstract: It is crucial to classify SE initiatives to better understand such a multifaceted phenomenon. However, previous attempts to classify SE initiatives seem not to contemplate the full SE complexity. Therefore, this study proposes a new classification using a broad taxonomic approach. It started by systematically selecting a set of initiatives. Then, an intensive search on secondary data about the initiatives selected was conducted in order to identify relevant attributes. Next, the attributes identified were successively aggregated resulting in four attribute groups. In the end, each initiative was analysed from the perspective of each attribute group, resulting in five SE categories: commodity intermediary, wealth redistributor, unique-service intermediary, skill redistributor, and decentralized commodity intermediary. Findings suggest that generalizations from studies focused on specific initiatives might be problematic, entrepreneurs should consider the characteristics of different SE categories to design appropriate platforms, and policymakers should avoid regulating all SE initiatives in a homogeneous manner. Chinese Abstract: 为更好地理解共享经济, 对共享经济举措进行分类是至关重要的.然而, 以前对共享经济举措进行分类的尝试似乎没有考虑到共享经济的复杂性.因此, 本研究提出一种新的分类方法, 使用广泛的分类学方法.它首先系统地选择了一组举措.然后, 为了识别相关的属性, 对所选举措的二手数据进行了深入的搜索.接下来, 将识别的属性依次聚合, 形成四个属性组.最后, 从各个属性组的角度分析了每一项举措, 得出五个共享经济类别:商品中介, 财富再分配, 独特服务中介, 技能再分配和去中心化商品中介.研究结果表明, 从侧重于特定举措的研究中归纳共享经济的分类可能是有问题的, 企业家应该考虑不同共享经济的类别的特征来设计合适的平台, 而政策制定者应该避免以一种同质的方式规范所有共享经济举措.